Efficacy and safety of cap-assisted endoscopic mucosal resection for superficial duodenal epithelial neoplasia ≤ 10 mm - Kimoto, Yoshiaki; Sawada, Rikimaru; Banjoya, Susumu; Iida, Toshifumi; Kimura, Tomoya; Furuta, Koichi; Nagae, Shinya; Ito, Yohei; Yamazaki, Hiroshi; Takeuchi, Nao; Takayanagi, Shunya; Kano, Yuki; Sakuno, Takashi; Ono, Kohei; Negishi, Ryoju; Ohno, Akiko; Sakai, Eiji; Minato, Yohei; Chiba, Hideyuki; Ohata, Ken (Endoscopy International Open, 2023)
Background and study aims Endoscopic treatment strategies for small superficial duodenal epithelial neoplasia (SDET) have not been established, and the R0 resection rates of all previously reported endoscopic techniques are somewhat low. Furthermore, no reports of cap-assisted endoscopic mucosal resection (EMRC), which is reportedly associated with a relatively high R0 resection rate, have been evaluated in sufficient numbers of patients. Therefore, we assessed the efficacy and safety of EMRC for SDETs ≤ 10 mm in a retrospective cohort study.Patients and methods We examined a prospectively maintained database and identified 248 consecutive patients (248 lesions) who had undergone endoscopic resection for SDETs ≤ 10 mm between January 2017 and June 2022. Our treatment strategy was consistent, with EMRC indicated for all SDETs ≤ 10 mm without non-lifting signs. The primary endpoint was the R0 resection rate.Results Overall, 20 lesions had non-lifting signs and were selected for endoscopic submucosal dissection, while the remaining 228 lesions were treated with EMRC. As a result of EMRC, the median tumor size was 5 mm, and the mean procedure time was 5 minutes. Most of the lesions (89.2%) were located in the descending part. The R0 resection rate was 97.4% (222/228 cases), and the en bloc resection rate was 99.6%. Only seven patients(3.1%) experienced adverse events (6 patients, delayed bleeding; 1 patient, acute pancreatitis), which were successfully managed without surgical intervention. Furthermore, no recurrences were observed.Conclusions We have demonstrated that EMRC is an effective and safe treatment for SDETs ≤ 10 mm that do not have non-lifting signs.
Keywords: Endoscopy Upper GI Tract; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE); Endoscopic resection (ESD, EMRc, ...); Endoscopy Small Bowel; Neoplasia